A strategy for using sensory analysis for category appraisal to develop new and improved products - Kumar, Rajesh (Kansas State University, 2020)
Food companies face the challenge of high product failure rates with 75%-90% of new food and beverage products failing within one year of launch. A majority of these products are either copy-cat, line extensions, or reformulation of existing market products. New product development (NPD) is mainly guided by marketing teams with short-term business horizons (e.g., create a new flavor for an existing product, change the color or shape, “create news”, short-term sales increase, etc.) at the expense of the true product innovations wanted and needed by consumers. The scientific insights of consumer needs and behavioral and psychological science are generally complicated, less understood, and marketing teams often overlook consumer-relevant aspects. Thus, considerable work is directed at finding new technologies or processes that can create a new product without knowing whether that new product will actually fulfill consumer needs. A comprehensive sensory science-based system for new food product development is required. This research is one part of a strategy to develop example strategies for sustainable, successful food product development to meet the needs of both consumers and industry. The overall research objectives were set in partnership with the industry to produce new snack ideas to create “global” product concepts. In this project, products were targeted at international markets to address larger consumer needs. The strategy for ideation and product roadmaps was driven by a detailed assessment of international market products. The initial rounds of research included products from diverse markets (e.g., the United States, China, India, Ghana, Mexico, Colombia, Italy, Thailand). After careful consideration of the market potential, the innovative orientation of Japan (JP) and South Korea (Republic of Korea) (SK) markets, in addition to those of the U.S. were chosen for further product exploration, assessment, and ideation. Food companies are continuously exploring international markets for new flavors, textures, packaging concepts, and products for inspiration. An effective way of gathering information is to conduct on-site research but international research presents many new challenges. Therefore, the first study was designed to determine and address the methodological challenges of conducting a product category assessment in an unfamiliar country (JP). The results (published) highlight the onsite challenges and potential solutions required to conduct international research in an unfamiliar country. For example, the country’s culture, law, language, customs, identity, people, product category of interest, data collection, product procurement, sampling, evaluation, and product shipment. Overall, the basic process template developed in this study is a valuable tool to perform a product category analysis in an unfamiliar country. The primary focus of this research was on texture which serves as a focus for the development of snack foods because flavor generally is easy to manipulate across various countries for similar snack products. A sensory texture lexicon for descriptive panels applicable to various processed and unprocessed snack foods (e.g., crackers, chips, vegetables, yogurt, etc.) was needed to profile snacks on sensory parameters. Thus, the second study (published) developed a multi-parameter and multi-sense sensory texture lexicon with trained descriptive panels. Eighty-five different snack and snack-like foods from eight countries were evaluated in detail. The results included the translation of the developed lexicon terms, definitions, techniques, and references terminologies into four major international languages (English, Hindi, Mandarin, and Spanish). Researchers and manufacturers can use the developed lexicon to assess snack food categories in various countries and can profile any new snack food developed to see if it matches or deviates from the target texture. In studies across countries and cultures, it is important to understand consumer terminologies and factors that can affect terminology when consumers describe their experience, concerns, and needs in snack foods. This research examined conceptual perception and linguistic barriers as key limiting factors in the cross-cultural food product development process which reduces the validity and general applicability of research results. The texture terms developed by sensory scientists are easy to translate at a scientific level to produce consistent information across cultures but are far too technical to be used to describe products to consumers. Thus, the third study (published) combined linguistic and contextual perception to explore consumer texture vocabularies. The results demonstrated that the vocabulary used by consumers to describe sensory characteristics of snack foods depends on context, culture, previous exposure, was specific to products, etc. We found divergent understanding and use of terms in each culture meaning that translation of English sensory terms without context can be problematic for non-English speaking cultures. The research results are important to understand as global companies want to market their new innovative products to local consumers as well as consumers in other cultures. The fourth study explored the robust JP and SK snack food markets to generate new snack concepts for global marketplaces. Ninety-six JP and 124 SK snack foods were categorized using sensory science tools such as product categorization, projective mapping (PM), and descriptive profiling. This research work demonstrated how developers can find white space in the marketplace by sorting in-market products using a 2-dimensional PM. Descriptive analysis was used to identify the main sensory attributes of the JP and SK snacks. The principal component analysis of descriptive data allows accessing product positioning and comparison of products in the marketplace to discover white spaces. Sensory profiles obtained from a wide range of snack foods can inspire researchers to create new product concepts with different and multi-sensory profiles. This work created a framework to discover white spaces in the marketplace and nurture new snack texture concepts to fill the identified white spaces by exploiting the main sensory attributes as product characteristics. In NPD, researchers frequently use statistical methods such as cluster analysis to segment consumers into groups based on some measure of product acceptance or to group products by sensory characteristics. However, researchers overlook the stability of clusters produced by clustering methods. Some statistical clustering methods can provide different results simply by re-running the analysis. The objects in the clusters (consumers or products) can change clusters, which influence the final solution and interpretation of data. The fifth study applied hierarchical agglomerative clustering (HAC), k-means (KM), and fuzzy clustering (FC) to a large descriptive sensory data set and compared cluster results obtained from these methods. The clustering frequency matrix was produced for KM solutions, and attributes (objects) were reorganized into groups via manual clustering (MC). Results showed that using various clustering methods and producing a clustering frequency matrix could be valuable in identifying reliable clusters in large data sets. The study concludes that results from one clustering trial and one method may not be reliable. Therefore, researchers must validate results using other cluster methods. The outcomes of this study can help to enhance confidence in results produced by clustering applications. Overall, the results of this research can help build sustainable product development systems based on examples using various food products and objectives for new food product development. By applying the research results industry and research institutions can make important progress in product development, and solve many complex issues related to the product development process.
Keywords: Sensory analysis; Consumer vocabulary; Snack foods; New food product development; Clustering methods; Marketplace